Revealing the Peculiarities of Female Students’ Physiological Characteristics with Different Somatotypes in the Absence of Compulsory Physical Activity at University - Banakh, Volodymyr; Iedynak, Gennadii; Galamanzhuk, Lesia; Blavt, Oksana; Huska, Mykhailo; Hrebik, Oleh; Dmytruk, Vitalii; Kovalchuk, Volodymyr (Physical Education Theory and Methodology, 2024)
Objectives. The purpose of the study was to determine the parameters of female students’ physiological characteristics with different somatotypes, which they achieved by exercising outside the university due to COVID-19 quarantine and air raids during the hostilities in Ukraine. Material and methods. The study involved 66 female students aged 17.8 ± 0.6 years, who belonged to different somatotypes and had no reservations about engaging in different amounts of physical activity. The Shtefko-Ostrovsky method, modified by S. Darskaja, was used to diagnose the somatotype. The necessary empirical data were obtained through the performing well-known functional tests that allowed to determine blood pressure, heart rate in different situations, vital capacity, vital capacity index, maximum isometric strength index, and Robinson index. The parameters of these characteristics were determined in female students with each of the four available somatotypes during the study, and each parameter was compared with different somatotypes. The testing was conducted at the beginning (January) and at the end (May-June) of the academic semester, but during one academic year. Results. At the beginning, and even more so at the end of the academic year, the parameters of the studied characteristics in female students with each of the available somatotypes differed from each other (p-values ranging at the level from 0.05 to 0.000). The volumes and conditions of physical activity used during the academic year did not lead to significant changes in the physiological characteristics of all female students, i.e. parameters remained at the previously achieved level. At the same time, the presence of peculiarities caused by the girl’s belonging to a certain somatotype was observed. Conclusions. Identifying the peculiarities in changes of female students’ physiological characteristics’ parameters, taking into account their somatotypes, is a perspective and significant direction for modernization of physical education at university. The obtained data will contribute to the individualization of the content and normative bases of physical education for female students, using information on the manifestation and change of parameters of various characteristics, including physiological ones.